Popular Film and Television Comedy. - Neale, Steve (Routledge, 1990)
How is comedy related to its institutional context? Neale and Krutnik, in this wide-ranging discussion of the genre, propose that comedy always involves deviation from aesthetic and cultural conventions and norms.